2023
DOI: 10.3389/fneur.2023.1204104
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in alpha-synucleinopathies: a systematic review

Kausar Raheel,
Gemma Deegan,
Irene Di Giulio
et al.

Abstract: BackgroundPast research indicates a higher prevalence, incidence, and severe clinical manifestations of alpha-synucleinopathies in men, leading to a suggestion of neuroprotective properties of female sex hormones (especially estrogen). The potential pathomechanisms of any such effect on alpha-synucleinopathies, however, are far from understood. With that aim, we undertook to systematically review, and to critically assess, contemporary evidence on sex and gender differences in alpha-synucleinopathies using a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 280 publications
0
0
0
Order By: Relevance
“…While differential genetic risk factors for PD in men vs women have not been demonstrated, sex-specific effects of genotype may exist 31,41 . 11 genomic loci have jointly been associated…”
Section: Female Predominance Among Lrrk2 Parkinsonism Cases Without E...mentioning
confidence: 99%
See 3 more Smart Citations
“…While differential genetic risk factors for PD in men vs women have not been demonstrated, sex-specific effects of genotype may exist 31,41 . 11 genomic loci have jointly been associated…”
Section: Female Predominance Among Lrrk2 Parkinsonism Cases Without E...mentioning
confidence: 99%
“…We found a female predominance among the LRRK2 parkinsonism cases without evidence for pathologic asyn. There is extensive literature that demonstrates that in individuals diagnosed with PD, sex differences exist for clinical, biomarker, neuropathological, or genetic endpoints 31 . Sex differences in LRRK2-parkinsonism cases are particularly notable.…”
Section: Female Predominance Among Lrrk2 Parkinsonism Cases Without E...mentioning
confidence: 99%
See 2 more Smart Citations
“…22 Most of abnormal motor events likely arise during phasic REM, which in RBD can vacillate from elementary movements to vivid dream enactments. 8,23 Historically, RBD was predominantly linked with male sex, [24][25][26][27] but that has been increasingly disputed with recognition that women tend to have a significantly later age of onset of RBD 28,29 and that they less frequently report dream-enacting behaviours. [29][30][31] Fernández-Arcos et al reported significantly more aggressive behavior in male RBD, and less so in women, who dreamt more about children in life-threatening contexts.…”
Section: Introductionmentioning
confidence: 99%